Orbital climate variability on the northeastern Tibetan Plateau across the Eocene-Oligocene transition - Ao, Hong; Dupont-Nivet, Guillaume (Dr.); Rohling, Eelco J.; Zhang, Peng; Ladant, Jean-Baptiste; Roberts, Andrew P.; Licht, Alexis; Liu, Qingsong; Liu, Zhonghui; Dekkers, Mark J.; Coxall, Helen K.; Jin, Zhangdong; et al. (Nature Communications, 2020)
The first major build-up of Antarctic glaciation occurred in two consecutive stages across the Eocene-Oligocene transition (EOT): the EOT-1 cooling event at similar to 34.1-33.9Ma and the Oi-1 glaciation event at similar to 33.8-33.6Ma. Detailed orbital-scale terrestrial environmental responses to these events remain poorly known. Here we present magnetic and geochemical climate records from the northeastern Tibetan Plateau margin that are dated precisely from similar to 35.5 to 31Ma by combined magneto- and astro-chronology. These records suggest a hydroclimate transition at similar to 33.7Ma from eccentricity dominated cycles to oscillations paced by a combination of eccentricity, obliquity, and precession, and confirm that major Asian aridification and cooling occurred at Oi-1. We conclude that this terrestrial orbital response transition coincided with a similar transition in the marine benthic delta O-18 record for global ice volume and deep-sea temperature variations. The dramatic reorganization of the Asian climate system coincident with Oi-1 was, thus, a response to coeval atmospheric CO2 decline and continental-scale Antarctic glaciation. Marine records indicate a greenhouse to icehouse climate transition at similar to 34 million years ago, but how the climate changed within continental interiors at this time is less well known. Here, the authors show an orbital climate response shift with aridification on the northeastern Tibetan Plateau during this time.